Anthropocentric paradigm of phraseological units in the literary translation (Eurasian Journal of Philology Science and Education, 2021)
This article represents theoretical problems of the anthropocentric paradigm. Considering anthropocentrismas person in the Universe center as a basis of all events and its reflection in language, theauthor investigates its functionality in relation to speech activity. Moreover, it is an attempt to shed lighton ways of research of the modern language personality and four various directions of the anthropocentricparadigm. In the article a term anthropocentrism is used as a principle of research of “the person inlanguage”, and it is more concrete “than the person in phraseology”. Phraseology research on the basisof the principle “in language” leads the person to development of the new direction, i.e. the anthropocentricphraseology. In the article it is also submitted the analysis of phraseological units in the anthropocentricparadigm on the basis of M. Auezov’s novel “Way of Abai”.Characterizing the direction of an anthropocentric paradigm in the field of phraseology, the authordistributes them in groups and reveals their correlation to psychology of person, the characteristic of anemotional state and traits of character.In particular, personal qualities of the person are assesseed onexamples, and there is analyzed the relation to environment, a place in society and collective. From thepoint of view of the anthropocentric paradigm the article considers the specifics of transfer of phraseologicalunits in a literary translation. To translate phraseological units from one language into another isone of the most difficult tasks. It is not enough to transfer complete meaning of the idioms in the translation;a translator should try to convey national spirit of the fixed phrase.Key words: anthropocentrism, language personality, linguistics, phraseological unit, literarytranslation